2005
DOI: 10.1007/s11663-005-0036-x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of MgO refractory in CaO-SiO2-MgO-FeO x and CaO-SiO2-Al2O3-MgO-FeO x slags under forced convection

Abstract: Experiments based on exposure of MgO to slags under forced convection flow conditions allowed the identification of different degradation mechanisms and the assessment of the role of Al 2 O 3 in the degradation process. Slag with no alumina present resulted in direct dissolution. Samples immersed in alumina containing slag underwent indirect dissolution, with a spinel forming at the MgO-slag interface. At 1530 °C, the spinel was not effective in reducing the corrosion rate, as the scattered spinel grains were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 8 publications
3
27
1
Order By: Relevance
“…This is in agreement with observations made during dissolution of polycrystalline MgO. [6,9] There is a large volume change associated with the transformation from MgO to MgAl 2 O 4 . The lattice parameter of the spinel (0.808 nm) [16] is almost double that of MgO (0.421 nm), [17] resulting in significant mismatch and strain at the interface, which could lead to fracture and detachment of the spinel crystals.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with observations made during dissolution of polycrystalline MgO. [6,9] There is a large volume change associated with the transformation from MgO to MgAl 2 O 4 . The lattice parameter of the spinel (0.808 nm) [16] is almost double that of MgO (0.421 nm), [17] resulting in significant mismatch and strain at the interface, which could lead to fracture and detachment of the spinel crystals.…”
supporting
confidence: 91%
“…[1][2][3][4][5][6] Evidence from quenched samples has suggested that the spinel forms at the liquid/solid interface, but then often becomes detached from the solid unless anchored by protrusions on the solid MgO surface. Therefore, this layer can be easily removed by forced liquid flow.…”
mentioning
confidence: 99%
“…[1][2][3][4] The formation of these spinel layers can be a process positive, slowing the refractory corrosion rate if they remain adhered to the refractory surface. Unfortunately, if the spinel oxide layer does not remain attached to the refractory, then it can become a source of inclusions for the steel.…”
Section: Introductionmentioning
confidence: 99%
“…From a thermodynamic perspective, the Marangoni convection at the slag-metal-refractory interface was less of a dominant factor determining the corrosion rate of the MgO-C refractory than the large solubility limit and the mass transfer in the slag phase both of which played a far more dominant role. In order to better understand the reaction kinetics between the MgO-C refractory and the molten slag, further experiments (such as the rotating finger experiments [22]) should be carried out.…”
Section: Resultsmentioning
confidence: 99%